The Civil Protection for the Elderly: a Reading in Legislative and Regulatory Texts Concerning Elderly People in Algeria - Belmohoub, Mohamed Tahar (Journal of Legal Studies and Researches, 2023)
This research paper aims to present the various civil and legal mechanisms for the protection of the elderly in Algeria by providing a reading of the legislative and regulatory texts relating to this group in society, in particular Law 10-12 on the protection of elderly persons and some of its regulatory texts.